Grammaticalization and Variation the Case of Mayan Motion Verbs - Hober, Nicole (Studia typologica ;, 2022)
Grammaticalization research looks back on a rich history, but recent empirical findings, as well as new insights from cognitive science and psycholinguistics, entice researchers to reassess and review what we know about the process. This book presents a detailed study of the grammaticalization of motion verbs in the Mayan languages. The focus lies on variation in the parallel grammaticalization of motion verbs into auxiliaries and directionals. It is demonstrated that the genetically related and areally close languages do not always grammaticalize source items in the same way - both from a formal and meaning perspective. The empirical findings suggest that traditional theories on grammaticalization do not capture the complex nature of the phenomenon entirely. Therefore, a Network Approach to grammaticalization is introduced which emphasizes a 'meaning-first' account. The approach seeks to combine the conceptual with the discourse-pragmatic while being firmly grounded in cognitive and psychological facts. New insights into the grammaticalization behavior of the world's languages are offered, while well-established notions and assumptions within the grammaticalization research paradigm are reviewed and challenged.